2018
DOI: 10.1073/pnas.1808760115
|View full text |Cite
|
Sign up to set email alerts
|

Forces drive basement membrane invasion in Caenorhabditis elegans

Abstract: SignificanceBasement membrane is a particular kind of sheet-like extracellular matrix that separates tissue compartments. Invasion of cells through basement membrane barriers is a key aspect of many normal and pathological processes, including organ development and cancer cell metastasis. Invasive protrusions are rich in actin, a cytoskeletal biopolymer, the self-assembly of which can produce force and remodel extracellular matrix. However, in the invasive protrusion, actin has been attributed a function in sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Further, reduction of Arp2/3 complex activity dramatically enhanced the AC MMPÀ invasion defect, indicating a crucial role for the Arp2/3 complex in driving MMPÀ invasion. Recent studies have suggested that F-actin-mediated forces play a role in breaching BM during AC invasion, but how these forces coordinate with MMP activity is unclear (Cá ceres et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, reduction of Arp2/3 complex activity dramatically enhanced the AC MMPÀ invasion defect, indicating a crucial role for the Arp2/3 complex in driving MMPÀ invasion. Recent studies have suggested that F-actin-mediated forces play a role in breaching BM during AC invasion, but how these forces coordinate with MMP activity is unclear (Cá ceres et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated the source of the physical forces that allow MMPÀ AC invasion. Branched actin networks, driven by Arp2/3 complex actin nucleation, produce migratory and invasive membrane protrusions and have recently been implicated as playing a role in AC invasion (Cá ceres et al, 2018;Swaney and Li, 2016).…”
Section: Loss Of Mmp Function Sensitizes Invasion To Arp2/3 Complex Amentioning
confidence: 99%
“…In this issue of Developmental Cell, Kelley et al (2019) deleted the five key MMPs and found to their surprise that even a quintuple knockout did not completely prevent crossing of the BM. The anchor cell instead formed an invasive protrusion that appears to breach BM through physical forces, shown to require branched actin networks produced by Arp2/3 in an accompanying study (Cá ceres et al, 2018).…”
mentioning
confidence: 88%
“…In a Caenorhabditis elegans model of BM invasion, cells could invade through the BM without proteases by applying force to deform the BM ( Cáceres et al, 2018 ; Kelley et al, 2019 ). In C. elegans , an anchor cell, or specialized uterine cell, crosses the BM during a precise time during development, making it a useful in vivo model to study BM invasion.…”
Section: Chemical and Physical Modes Of Bm Invasionmentioning
confidence: 99%